2011
DOI: 10.1099/vir.0.033332-0
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus IAP1 induces caspase-dependent apoptosis in insect cells

Abstract: Baculoviruses encode inhibitors of apoptosis (IAPs), which are classified into five groups, IAP1-5, based on their sequence homology. Most of the baculovirus IAPs with anti-apoptotic functions belong to the IAP3 group, with certain exceptions. The functional roles of IAPs from other groups during virus infection have not been well established. We have previously shown that Hyphantria cunea multiple nucleopolyhedrovirus (HycuMNPV) encodes three iap genes, hycu-iap1, hycu-iap2 and hycu-iap3, and that only Hycu-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 60 publications
(80 reference statements)
3
36
0
Order By: Relevance
“…In vAchrf-1-infected Ld652Y cells, the levels of both full-length and cleaved Ld-Dronc decreased gradually from 24 to 120 h postinfection (Fig. 4B), likely due either to apoptosis induction late in the infection cycle (51,53) or to the shutdown of host protein synthesis, which is often observed during progeny virus replication (54)(55)(56). In contrast, cleaved Ld-Dronc corresponding to prodomain and p20 domain was not detected in LdMNPV-infected Ld652Y cells (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In vAchrf-1-infected Ld652Y cells, the levels of both full-length and cleaved Ld-Dronc decreased gradually from 24 to 120 h postinfection (Fig. 4B), likely due either to apoptosis induction late in the infection cycle (51,53) or to the shutdown of host protein synthesis, which is often observed during progeny virus replication (54)(55)(56). In contrast, cleaved Ld-Dronc corresponding to prodomain and p20 domain was not detected in LdMNPV-infected Ld652Y cells (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…We previously found that IAP1s from diverse NPVs and IAP2 and IAP3 from LdMNPV trigger apoptosis when transiently expressed in several lepidopteran insect cells, accompanied by the activation of caspase-3-like protease and proteolytic processing of endogenous Dronc (48,51). These baculovirus IAPs are unable to suppress apoptosis triggered by baculovirus infections and may trigger apoptosis by replacing the cellular IAPs, which presumably bind to Dronc and negatively regulate the activation of Dronc in nonapoptotic cells (48,51,57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baculoviruses are able to manipulate the cellular environment to enhance their infection (Thiem, 2009), e.g. by inhibiting cell cycle progression (Prikhod'ko & Miller, 1998), inducing DNA damage response (Huang et al, 2011), blocking apoptosis (Ikeda et al, 2011) and inducing shutoff of host gene expression (Ooi & Miller, 1988). They are also able to manipulate host physiology and behaviour through the expression of various viral proteins (Kamita et al, 2005;Katsuma et al, 2012;O'Reilly & Miller, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…5 However, transient expression of Ac-IAP1 was capable of inducing apoptosis and stimulating caspase-3 protease activity in various lepidopteran and dipteran cell lines. 15 So, the function of AcIAPs remained unknown. In this study, Bac-to-Bac baculovirus expression system was used to generate two recombinant baculoviruses, AcMNPV-iap1-egfp and AcMNPV-iap2-egfp, the effects of AcMNPV-iap1/2-egfp on Sf9 (Spodoptera frugiperda 9) cells and Helicoverpa armigera larvae were examined, and the function of BIR2 domain in Ac-IAP2 was analyzed preliminarily, which further conrmed the role of Ac-IAP1/2 during viral infection and offered experimental basis for using AcMNPViap2-egfp as a stronger insecticide and a more effective insect cell expression system.…”
Section: Introductionmentioning
confidence: 99%